2013
DOI: 10.1080/08874417.2013.11645649
|View full text |Cite
|
Sign up to set email alerts
|

Risks in Enterprise Cloud Computing: The Perspective of it Experts

Abstract: Cloud computing has become an increasingly prevalent topic in recent years. However, migrating hitherto internal IT data and applications to the cloud is associated with a wide range of risks and challenges. The study reported in this paper aims to explore potential risks that organisations may encounter during cloud computing adoption, as well as to assess and prioritise these risks, from the perspective of IT practitioners and consultants. A questionnaire was designed and distributed to a group of 295 highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(76 citation statements)
references
References 27 publications
0
76
0
Order By: Relevance
“…In fact, the E-government cloud solution was initiated by the top management. Top management that recognizes the advantages of E-government cloud will likely allocate the necessary resources for its adoption and influence the organization's members to implement the change (Dutta et al, 2013). In the interview, we got that top managers although were lack of understanding of the cloud computing, usually made decision of adoption of cloud with the pressure of superiors.…”
Section: ) Top Management Supportmentioning
confidence: 98%
“…In fact, the E-government cloud solution was initiated by the top management. Top management that recognizes the advantages of E-government cloud will likely allocate the necessary resources for its adoption and influence the organization's members to implement the change (Dutta et al, 2013). In the interview, we got that top managers although were lack of understanding of the cloud computing, usually made decision of adoption of cloud with the pressure of superiors.…”
Section: ) Top Management Supportmentioning
confidence: 98%
“…Cloud computing adoption decisions are challenging due to various concerns such as cost, confidentiality and control (Khajeh-Hosseini et al 2012). Organisations that adopt, or migrate to, cloud computing services often do not understand the resulting risks (Dutta et al 2013). Hence, decisions to migrate existing enterprise systems to SaaS solutions can be complicated as evaluating the benefits, risks and costs of using cloud computing is not straightforward (Khajeh-Hosseini et al 2011).…”
Section: Decision Framework and Tools For Supporting Cloud Saas Migrmentioning
confidence: 99%
“…European Network and Information Security Agency (ENISA) and Cloud Security Alliance (CSA) have found that lock-in risks and insufficient due diligence were among the top threats in cloud computing (Dutta et al 2013;Baldwin et al 2013). Cloud computing adoption decisions are challenging due to various concerns such as cost, confidentiality and control (Khajeh-Hosseini et al 2012).…”
Section: Decision Framework and Tools For Supporting Cloud Saas Migrmentioning
confidence: 99%
“…Due to these problems, a radical change is required within ERP framework to enhance ERP infrastructural and functionality. The emergence of cloud computing is considered to be the best suited option to overcome ERP systems discrepancies [1,2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Due to these problems, a radical change is required within ERP framework to enhance ERP infrastructural and functionality. The emergence of cloud computing is considered to be the best suited option to overcome ERP systems discrepancies [1,2,3,4].Cloud computing is a technique for enabling convenient, on-demand network access to a shared pool of configurable computing resources that can be rapidly provisioned and released with minimal management effort or service provider interaction. Cloud computing is an alternative of deploying applications and systems on-premises.…”
mentioning
confidence: 99%